Rescuing the heart: HIET in undifferentiated shock from beta-blocker and dapagliflozin overdose in acute coronary syndrome - Arihant Jain; Swetha Ramesh; Shruti Singh; Anas Mohammed Muthanikkatt; N. Balamurugan (JEM Reports)
Background: A 60-year-old female with ischemic dilated cardiomyopathy and diabetes mellitus presented with acute coronary syndrome (ACS) complicated by severe ventricular tachyarrhythmia after ingesting an excessive dose of metoprolol (250 mg) and dapagliflozin (100 mg). Despite metoprolol's dose being below traditional toxic thresholds, chronic beta-blocker therapy likely amplified its negative inotropic effects, leading to refractory hypotension overdose of metoprolol was not the cause of V tach, rather it was because of underlying ACS. Initial resuscitation with synchronized cardioversion and noradrenaline infusion failed to stabilize her blood pressure. High-Dose Insulin Euglycemia Therapy (HIET) was initiated as a salvage measure, resulting in significant hemodynamic improvement within 2–3 hours, increased left ventricular ejection fraction (LVEF) on repeat echocardiography, and blood pressure stabilization. Case-report: The patient presented with severe ventricular tachyarrhythmia and persistent hypotension following an overdose of metoprolol and dapagliflozin. Despite initial treatments, her condition did not improve. HIET was initiated and led to rapid hemodynamic stabilization and improved LVEF within a few hours. Lidocaine infusion was added to manage the prolonged QT interval and suppress further arrhythmias. Her condition gradually improved over the following days, with resolution of hypotension and arrhythmias. She was discharged after four days of inpatient care. Why should an emergency physician be aware of this ?: This case highlights that chronic beta-blocker use can lead to refractory hypotension even at non-toxic overdose levels and demonstrates the efficacy of HIET as a critical, lifesaving intervention for shock and cardiac recovery in overdose of B- blocker.